Hybrid Cloud Data Security Model Using Splitting Technique - Mishra, Siddharth; Sharma, Puneet (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is an enticing technology that delivers services over the internet. It allows business organizations to use different applications and store information without accessing their personal files. In the recent years IT organizations prefer to move towards the adoption of Hybrid Cloud as it can be easily incorporated with the existing infrastructures of the enterprises. The cost of the implementation of hybrid cloud is quite low and it also provides the advantages of both public and private clouds. However, with the measurement of power, stability and the security of cloud one cannot ignore unlike coercion to user’s data on cloud storage. In this paper, a security model has been proposed that secures sensitive and critical data with the help of symmetric cryptography and data splitting techniques. It also uses multi cloud service providers for the protection of overall cloud model. Data to be stored in the cloud will be first encrypted using AES encryption and then it will be split into numerous chunks. After splitting, these chunks of data will be stored in dissimilar clouds in a random manner.